2015
DOI: 10.17275/per.14.19.2.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Instructional Technology and Material Design Course to Teacher Candidates’ Gaining of Technological Pedagogical Content Knowledge Competencies

Abstract: The aim of this study is to determine Technological Pedagogical Content Knowledge (TPACK) Competencies of teacher candidates in Turkish Teaching department of Mevlana (Rumi) University and the effect of Instructional Technology and Material Design (ITMD) Course on TPACK. The study is a study of quantitative type and single-group pretest-posttest experimental design has been used. The study has been conducted in the spring semester of 2013/2014 academic year, candidates who are studying in 2nd class of Turkish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…It can be assumed that the participants had already acquired the necessary knowledge of ICT usage after the intervention. This result is consistent with the findings of the studies done by Baran et al (2011), Papanikolaou (2014), Sezer (2015), and Tozkoparan et al (2015) who all found that TPACK model plays a leading role on the subject of teachers' needs about technology, pedagogy and content in order to ensure professional development of teachers. Ultimately, TPACK has provided a valuable tool for assessing teacher knowledge in the area of technology integration.…”
Section: Discussionsupporting
confidence: 92%
“…It can be assumed that the participants had already acquired the necessary knowledge of ICT usage after the intervention. This result is consistent with the findings of the studies done by Baran et al (2011), Papanikolaou (2014), Sezer (2015), and Tozkoparan et al (2015) who all found that TPACK model plays a leading role on the subject of teachers' needs about technology, pedagogy and content in order to ensure professional development of teachers. Ultimately, TPACK has provided a valuable tool for assessing teacher knowledge in the area of technology integration.…”
Section: Discussionsupporting
confidence: 92%